Penguatan Kapasitas Organisasi Perangkat Gampong Seunebok Kecamatan Blang Mangat - Mauludi; Alwi; Syamsuddin; Hadilpa, Iqhpy; Uthariani, Asyfi Nadya (PASAI : Jurnal Pengabdian kepada Masyarakat, 2022)
Community Service Activities are carried out in Seunebok Gampong, Blang Mangat District, Lhokseumawe City with the target village. This activity is carried out to train and broaden the knowledge, skills, and insights of Gampong apparatus in managing, and increasing organizational abilities so that they are able to make the organization a place for expressing their respective expertise and can run various programs in overcoming various problems that occur. The contents of the training material cover the areas of organization, management, and leadership using lecture and discussion/FGD methods. This community service activity can contribute to strengthening Gampong apparatus organizations in facing increasingly competitive challenges and competitiveness in all aspects of life.